The Implementation of Ornamental Motif Learning in Cultural Arts Subjects for Grade VII at SMP Negeri 3 Guguak - Maysarah Maysarah; Chairul Haq; Nefri Anra Saputra; Asmidar Asmidar (Gorga : Jurnal Seni Rupa, 2026)
This study investigates the implementation of ornamental motif learning within the Cultural Arts subject for Grade VII students at SMP Negeri 3 Guguak District, adhering to the Merdeka Curriculum framework. The research objective is to elucidate the planning, execution, and challenges encountered during the learning process of ornamental motifs. Employing a descriptive qualitative approach, data were collected through observation and documentation, sourced from the learning process, teaching materials, and students’ artworks. The study revealed that ornamental motif learning at SMP Negeri 3 Guguak was implemented through a sequential series of activities, commencing with an introduction, sketching, and artwork completion. The learning process offers students opportunities to enhance their visual creativity, commencing from sketching to the completion of final artworks. Challenges identified include constraints in tools and materials, variations in students’ abilities, and limited instructional time. Nevertheless, through meticulous planning and intensive guidance, the learning process remains effective and facilitates the development of students’ creativity and visual skills.